Administrative practices and problems of private secondary school principals of Lanao del Sur and Marawi City - Batara, Corazon (Manzano) 1937- (s.n., 1973)
This paper identified some administrative practices and problems of private secondary school principals of Lanao del Sur and Marawi City particularly in the areas of recruitment, selection and retention of teachers, programming and distribution of teachers' schedule, improving the teaching-learning conditions, management of the school plant, preparation of students' records, reports of students' progress to the parents, teachers' relations with the community and students' discipline.